TI_GERICHTE 60.2004.122 vom 7. November 2005 , istanza di indennità per ingiusto procedimento. spese legali. torto morale. regresso. - TI Tribunale d'appello (2005)
istanza di indennità per ingiusto procedimento. spese legali. torto morale. regresso.